Electrochromic device and method for manufacturing the same
Patent Information
- Application Number
- CN202611304312.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-10-13
AI Technical Summary
[0003]目前的研究多采用单一阳离子体系,难以同时兼顾响应速度与光学调制幅度:以Zn2+为代表的多价金属离子具有较高的光学调制幅度,但其与溶剂及晶格间相互作用强、脱溶剂化与迁移能垒高,导致响应迟缓;而以NH4+为代表的轻质离子迁移速率快、响应迅速,但受限于较小的离子嵌入量,光学调制幅度偏低
[0031]本发明制备的电致变色器件以纳米级尺寸的量子点(如氧化钨量子点)作为无机电致变色层,包含NH4+和Zn2+阳离子的凝胶电解质作为电解质层,Zn金属网作为离子存储层,量子点的大比表面积提供了丰富的离子嵌入/脱出活性位点,混合离子电解质显著降低Zn²⁺的脱溶剂化能垒及电极/电解质界面处的迁移能垒,锌网提供了均匀稳定的电场,三者协同作用,有效降低了器件的响应时间。
Smart Images

Figure CN122902138A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochromic technology, specifically to an electrochromic device and its preparation method. Background Technology
[0002] Electrochromic devices can undergo reversible color changes under the influence of an applied electric field, thereby enabling dynamic management of solar radiation energy. This intelligent response characteristic allows them to adjust indoor lighting and temperature in real time according to weather conditions and individual needs, creating a comfortable and healthy indoor environment while significantly reducing building energy consumption. However, existing electrochromic devices, especially inorganic ones, while possessing advantages such as good cycle stability, strong UV resistance, wide optical modulation range, and long lifespan, generally suffer from slow response speeds. This severely restricts the dynamic control capabilities of electrochromic devices and has become one of the main bottlenecks for their large-scale application. The electrolyte, as a core component of electrochromic devices, has a decisive influence on device performance due to the types and composition of its ions.
[0003] Current research mostly employs single-cation systems, making it difficult to simultaneously achieve both response speed and optical modulation amplitude: using Zn 2+ Multivalent metal ions, represented by NH4+, exhibit high optical modulation amplitude, but their strong interactions with solvents and lattice, along with high desolvation and migration barriers, lead to sluggish response; while NH4+... + Light ions, represented by [specific examples], exhibit fast migration rates and rapid responses, but their optical modulation amplitude is limited by relatively small ion intercalation amounts. Therefore, developing a composite electrolyte that can synergistically reduce the ion migration energy barrier while balancing rapid response and high optical modulation amplitude, and clarifying its preparation method and application in electrochromic devices, is of significant research value for overcoming the response bottleneck of inorganic electrochromic devices and improving their overall performance. Summary of the Invention
[0004] The purpose of this invention is to provide an electrochromic device and its preparation method to solve the problems mentioned in the background art.
[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution:
[0006] An electrochromic device includes a first transparent conductive electrode, an inorganic electrochromic layer, an electrolyte layer, an ion storage layer, and a second transparent conductive electrode arranged sequentially from top to bottom.
[0007] The first transparent conductive electrode includes a first transparent substrate layer and a first conductive layer. The first transparent substrate layer of the first transparent conductive electrode is located on the top layer of the device, and the first conductive layer is attached to the inorganic electrochromic layer. The second transparent conductive electrode includes a second transparent substrate layer and a second conductive layer. The second transparent substrate layer is located on the bottom layer of the device, and the second conductive layer is attached to the ion storage layer.
[0008] Furthermore, the materials of the first transparent substrate layer and the second transparent substrate layer are selected from one or more of glass, quartz, polymethyl methacrylate, polycarbonate, and polyethylene terephthalate.
[0009] Furthermore, the sheet resistance of the first conductive layer and the second conductive layer is 5~20Ω / square.
[0010] Furthermore, the thickness of the first conductive layer and the second conductive layer is 100~300nm.
[0011] Furthermore, the materials of the first conductive layer and the second conductive layer are selected from any one or more of ITO, FTO, AZO, metal, conductive polymer, and carbon nanotubes.
[0012] Furthermore, the metal includes, but is not limited to, metal mesh and nanowires.
[0013] Furthermore, the conductive polymer includes, but is not limited to, polypyrrole, polythiophene, and polyaniline.
[0014] Furthermore, the inorganic electrochromic layer has a thickness of 100~1500nm, and the material of the inorganic electrochromic layer is selected from any one or more of tungsten oxide quantum dots, molybdenum oxide quantum dots, vanadium oxide quantum dots, and titanium oxide quantum dots.
[0015] Furthermore, the thickness of the electrolyte layer is 100~2000µm, and the cations in the electrolyte layer are NH4. + Zn 2+ Two kinds.
[0016] Furthermore, the method for preparing the electrolyte layer includes the following steps:
[0017] S1: Trimethyl phosphate (TMP) and water are mixed to obtain a solvent;
[0018] S2: Add zinc salt and ammonium salt as electrolytes to the solvent of S1 and stir to obtain an electrolyte solution;
[0019] S3: Add polyethylene glycol diacrylate (PEGDA) and a photoinitiator to the electrolyte solution in S2, stir until homogeneous to obtain a gel electrolyte solution, and polymerize under ultraviolet light to obtain an electrolyte layer.
[0020] Further, in S1, trimethyl phosphate and water are mixed in a volume ratio of 7:3 to obtain a solvent.
[0021] Furthermore, in S2, the zinc salt concentration in the electrolyte solution is 0.5M, the ammonium salt concentration is 0.5M, and the molar ratio of zinc salt to ammonium salt is 1:1.
[0022] Furthermore, in S2, the zinc salt is zinc trifluoromethanesulfonate, and the ammonium salt is ammonium trifluoromethanesulfonate.
[0023] Furthermore, the mass ratio of polyethylene glycol diacrylate to electrolyte is 10:100.
[0024] Furthermore, the thickness of the ion storage layer is 0.1~10μm.
[0025] Furthermore, the material of the ion storage layer is selected from one or more of the following: metal electrode, polyaniline electrode, nickel oxide electrode, and Prussian blue electrode.
[0026] Furthermore, the method for preparing the electrochromic device includes the following steps:
[0027] Step 1: Prepare an inorganic electrochromic layer on the surface of the first conductive layer of the first transparent conductive electrode to obtain the first transparent conductive electrode / inorganic electrochromic layer;
[0028] Step 2: An ion storage layer is prepared on the surface of the second conductive layer of the second transparent conductive electrode to obtain the ion storage layer / second transparent conductive electrode;
[0029] Step 3: Seal the first transparent conductive electrode / inorganic electrochromic layer and the ion storage layer / second transparent conductive electrode to form a hollow sandwich structure; then inject a gel electrolyte solution into the cavity of the hollow sandwich structure and solidify it to form an electrolyte layer, thus obtaining the electrochromic device.
[0030] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0031] The electrochromic device prepared by this invention uses nanoscale quantum dots (such as tungsten oxide quantum dots) as the inorganic electrochromic layer, containing NH4. + and Zn 2+ The cation gel electrolyte serves as the electrolyte layer, and the Zn metal mesh serves as the ion storage layer. The large specific surface area of quantum dots provides abundant ion insertion / extraction active sites. The mixed ion electrolyte significantly reduces the desolvation energy barrier of Zn²⁺ and the migration energy barrier at the electrode / electrolyte interface. The zinc mesh provides a uniform and stable electric field. The three work synergistically to effectively reduce the response time of the device.
[0032] When a negative voltage is applied to the device, cations and electrons in the mixed electrolyte migrate synchronously to the inorganic electrochromic layer and undergo an electrochemical intercalation reaction, causing changes in the valence state and optical band gap of the electrochromic layer material, achieving a transition from a high-transmittance state to a low-transmittance state. Simultaneously, the ion storage layer releases cations to maintain charge balance. When a reverse voltage is applied, the above process is reversed, ions are extracted from the electrochromic layer, and the device returns to the high-transmittance state.
[0033] In preparing the gel electrolyte, this invention uses a trimethyl phosphate / water system as the solvent for the electrolyte solution, taking into account both the good cycling stability of trimethyl phosphate and the fast response time of the aqueous system. Compared to other organic solvents, the P=O group in the TMP molecule has a lone pair of electrons, which can act as a Lewis base and react with Zn. 2+ TMP interacts with NH4⁺ through coordination-solvation, effectively weakening the electrostatic attraction between cations and anions in zinc and ammonium salts, promoting ion pair dissociation, and increasing the concentration of free carriers, thereby ensuring high ionic conductivity of the electrolyte. Simultaneously, TMP exhibits moderate coordination ability: compared to strong coordination solvents, the solvation shell formed by TMP is more prone to desolvation at the electrode / electrolyte interface, which helps reduce the interfacial ion migration barrier. This characteristic is crucial for achieving rapid device response—Zn 2+ NH4⁺ can rapidly desorb from the solvated state and embed into the electrochromic layer upon application of voltage, thus significantly shortening the response time. Furthermore, TMP exhibits low corrosivity to the zinc mesh electrode, which is beneficial for maintaining the long-term electrochemical activity of the ion storage layer and the cycle life of the device. In summary, TMP achieves a good balance between promoting ion dissociation and lowering the desolvation energy barrier, making it a suitable solvent choice for the mixed ion electrolyte system of this invention. Attached Figure Description
[0034] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings:
[0035] Figure 1 This is a schematic diagram of the structure of the fast-response electrochromic device provided by the present invention;
[0036] Figure 2 The X-ray diffraction pattern of the inorganic electrochromic layer prepared in Example 3 of this invention;
[0037] Figure 3 This is a cross-sectional view of the inorganic electrochromic layer prepared in Example 3 of the present invention;
[0038] Figure 4 The X-ray diffraction pattern of the ion storage layer prepared in Example 3 of this invention;
[0039] Figure 5This is a surface morphology diagram of the ion storage layer prepared in Example 3 of the present invention;
[0040] Figure 6 The transmittance spectra of the inorganic electrochromic layer prepared in Example 3 of the present invention at 1.5V, 0.6V and 0.1V respectively;
[0041] Figure 7 The response time diagram of the inorganic electrochromic layer prepared in Example 3 of the present invention under 633nm wavelength light;
[0042] Figure 8 The transmittance spectra of the electrochromic device prepared in Example 3 of the present invention at 1.5V, 0.6V and 0.1V respectively;
[0043] Figure 9 The response time diagram of the electrochromic device prepared in Example 3 of the present invention under 633nm wavelength light;
[0044] Figure 10 Digital photographs of the electrochromic device prepared in Example 3 of the present invention in three states;
[0045] Figure 11 This is a cycle life diagram of the electrochromic device prepared in Example 3 of the present invention. Detailed Implementation
[0046] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0047] The electrochromic device structure provided in the embodiments of the present invention is shown in the figure below. Figure 1 As shown, from top to bottom, it includes a first transparent conductive electrode, an inorganic electrochromic layer, an electrolyte layer, an ion storage layer, and a second transparent conductive electrode.
[0048] In the first and second transparent conductive electrodes, the first and second transparent substrate layers are both made of soda-lime glass, the first and second conductive layers are both made of ITO, the sheet resistance of the first and second conductive layers is 17Ω / square, and the thickness of the conductive layer is 100nm.
[0049] The inorganic electrochromic layer is WO3QDs with a thickness of 419 nm;
[0050] The electrolyte layer is a 1mm thick gel electrolyte layer;
[0051] The ion storage layer is a zinc-stainless steel mesh with a zinc layer thickness of 4μm.
[0052] The method for preparing the above-mentioned electrochromic device includes the following steps:
[0053] Step 1: Fabrication of the first transparent conductive electrode / inorganic electrochromic layer:
[0054] S11: Clean the first transparent conductive electrode and the stainless steel mesh sequentially with deionized water, acetone, isopropanol and anhydrous ethanol for 20 minutes each, then place them in a vacuum drying oven at 60℃ to dry. After drying, seal them with plastic film and place them in a drying cabinet for later use.
[0055] S12: Dissolve 0.02 mol sodium tungstate in 20 ml of deionized water and stir continuously until completely dissolved. Then, slowly add 5 ml of concentrated hydrochloric acid (12 mol / L, 36% by mass) to the solution while stirring until no new precipitate forms. Subsequently, repeatedly centrifuge and wash the precipitate with deionized water and anhydrous ethanol until the pH value exceeds 3. After washing, transfer the precipitate to 40 ml of ethylene glycol and heat and stir at 90°C until the precipitate is completely dissolved, forming a colorless and transparent solution. Pour this solution into a 100 ml high-pressure reactor lined with polytetrafluoroethylene (PTFE) and conduct a solvothermal reaction at 180°C in a forced-air oven for 48 hours. After the reaction is complete, allow the reactor to cool naturally to room temperature to obtain a transparent, pale yellow tungsten oxide quantum dot (WO3QDs) / ethylene glycol solution.
[0056] A certain amount of WO3QDs / ethylene glycol solution was placed into a clean dialysis bag and sealed with a special sealing clip. The dialysis bag was immersed in a corresponding volume of deionized water and dialyzed for 12 hours, with continuous stirring to accelerate the dialysis process and the water changed every 6 hours. After dialysis, an aqueous solution of WO3QDs was obtained. To ensure the long-term stability of WO3QDs and facilitate subsequent ultrasonic spraying, an equal volume of isopropanol solution was added to the obtained WO3QDs aqueous solution to obtain a stable WO3QDs spraying solution. The first transparent conductive electrode was treated with ultraviolet ozone and placed on a heating stage preheated to 90°C. The WO3QDs spraying solution was uniformly sprayed onto the surface of the first conductive layer of the first transparent conductive electrode using an ultrasonic spraying device at a flow rate of 0.1 mL / min, a spraying height of 10 cm, and 100 sprays, forming a uniform WO3QD film as an inorganic electrochromic layer, thus obtaining the first transparent conductive electrode / inorganic electrochromic layer.
[0057] Step 2: Fabrication of the ion storage layer / second transparent conductive electrode:
[0058] An electrodeposition solution was prepared by dissolving 3g zinc sulfate heptahydrate, 3g sodium sulfate, 0.08g polyethyleneimine aqueous solution, and 0.5g boric acid in 20mL of deionized water. Then, using a stainless steel mesh treated with UV ozone as the working electrode and zinc foil as the counter electrode, a constant potential deposition was performed for 3600s at -0.2V. After deposition, the uniformly deposited zinc stainless steel mesh was removed, its surface was gently rinsed with deionized water, and then dried in air to obtain an ion storage layer. The ion storage layer was then bonded to the surface of the second conductive layer of the second transparent conductive electrode using double-sided cotton paper adhesive, resulting in an ion storage layer / second transparent conductive electrode.
[0059] Step 3: Prepare the electrolyte layer:
[0060] Trimethyl phosphate and deionized water were stirred and mixed to obtain a solvent; zinc trifluoromethanesulfonate and ammonium trifluoromethanesulfonate were added to obtain an electrolyte solution; polyethylene glycol diacrylate and photoinitiator 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone were added to the electrolyte solution to obtain a gel electrolyte solution; in the gel electrolyte solution, the mass ratio of polyethylene glycol diacrylate to electrolyte was 10:100.
[0061] Step 4: Assemble and fabricate electrochromic devices:
[0062] The first transparent conductive electrode / inorganic electrochromic layer and the ion storage layer / second transparent conductive electrode are sealed with 3M tape to form a hollow sandwich structure; then, a gel electrolyte solution is injected into the cavity of the hollow sandwich structure; under a light intensity of 50mW / cm², the solution is applied. 2 The electrolyte is solidified into a gel electrolyte by irradiating it with ultraviolet light for 60 seconds, thus obtaining the electrochromic device.
[0063] Example 1: In the system of the present invention, the solvent must simultaneously meet the following requirements: for Zn 2+ and NH4 + Both cations and their corresponding salts exhibit good solubility and dissociation capabilities, a wide electrochemical window to avoid side reactions within the operating voltage range, low volatility to ensure long-term device stability, inherent flame retardancy to meet safety requirements in the construction and transportation sectors, and compatibility with the PEGDA polymerization system to ensure the formation of a uniform and transparent gel electrolyte layer after in-situ photocuring. Therefore, this embodiment investigates the effects of different solvents on the performance of the electrolyte layer.
[0064] In this embodiment, four reagents—trimethyl phosphate (TMP), dimethyl sulfoxide (DMSO), ethylene glycol (EG), and propylene carbonate (PC)—were used as solvents to prepare gel electrolytes.
[0065] The preparation method of the gel electrolyte solution is as follows:
[0066] Trimethyl phosphate (TMP) and water were mixed at a volume ratio of 7:3 to obtain a solvent; zinc trifluoromethanesulfonate and ammonium trifluoromethanesulfonate were added to the solvent of S1 as electrolytes, and the mixture was stirred to obtain an electrolyte solution; in the electrolyte solution, Zn 2+ Concentration of 0.5M, NH4 + The concentration is 0.5M. Polyethylene glycol diacrylate (molecular weight 400) and 0.1g of photoinitiator 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone are added to the electrolyte solution to obtain a gel electrolyte solution, wherein the polyethylene glycol diacrylate accounts for 10% of the total mass of the electrolyte.
[0067] Dimethyl sulfoxide (DMSO), ethylene glycol (EG), and propylene carbonate (PC) were used instead of trimethyl phosphate (TMP) to obtain the corresponding gel electrolyte solutions. Electrolyte layers were prepared using the method described in step 3 above, and the performance of each group was compared. The results are as follows:
[0068] Although DMSO has a high dielectric constant and excellent ion solubility, it also has a certain inhibitory effect on free radical polymerization during the UV curing process, resulting in uneven gel electrolyte film formation.
[0069] EG has good solubility for zinc trifluoromethanesulfonate and ammonium trifluoromethanesulfonate, but its molecules contain a large number of hydroxyl groups and have high viscosity, resulting in low ionic conductivity, which is not conducive to rapid ion transport and leads to a slow response time.
[0070] PC exhibits poor solubility for zinc trifluoromethanesulfonate and ammonium trifluoromethanesulfonate, resulting in a cloudy electrolyte that does not meet the requirement for a transparent electrolyte in electrochromic processes.
[0071] TMP performs best overall among the above indicators, therefore TMP is the preferred electrolyte solvent.
[0072] Example 2: In this example, TMP was used as the electrolyte solvent. In order to investigate the effect of water content and ion concentration in the solvent on the performance of the electrolyte layer, different electrolyte solutions were prepared according to the components in Table 1 and were numbered 1 to 8 respectively.
[0073] Table 1.
[0074] Serial Number Water content (by volume) in the solvent <![CDATA[Zn in the solvent 2+ concentration]]> <![CDATA[NH4 in the solvent + concentration]]> 1 30% 0.5M 0.5M 2 0 0.5M 0.5M 3 20% 0.5M 0.5M 4 40% 0.5M 0.5M 5 30% 1M / 6 30% / 1M 7 30% 0.5M 0.25M 8 30% 0.5M 0.75M
[0075] WO3QD films were prepared according to the method in step S12 above, and the spectra / response times of the WO3QD films were investigated, as shown in Table 2.
[0076] Test Method: A two-electrode test method was adopted, using a WO3QD thin film as the working electrode and a high-purity zinc sheet as the counter electrode. Both were placed together in a specially designed cuvette containing an electrolyte solution (the electrolyte solutions in the cuvette correspond to the electrolyte components in Table 1) to test the electrochromic performance. During the test, a specified voltage was applied to the test system using a CHI760E electrochemical workstation, and an AV1050+ UV-Vis-NIR spectrophotometer was used to perform optical performance testing and data processing on the electrochromic thin film and electrochromic device.
[0077] Table 2.
[0078] Serial Number Ionic conductivity (mS / cm) Transmittance in faded state (%) Colored transmittance (%) Optical modulation amplitude (%) Coloring time (s) Fading time (s) 1000C Cycle Stability (%) 1 12.8 96 7.2 88.8 10.6 6.8 81.1 2 4.8 96 64.9 31.1 16.8 25.6 / 3 8.2 96 17.1 78.9 15.2 9.6 82.6 4 18.6 96 6.1 89.9 5.2 6.4 61.2 5 9.5 96 22.9 73.1 19.4 11.9 82.2% 6 16.3 96 15.4 80.6 7 7.4 80.7% 7 11.1 96 10.0 86 12.9 7 81.5% 8 14.5 96 11.3 84.7 10 6.8 79.9%
[0079] Since the electrolyte solution system corresponding to serial number 2 does not contain water, Zn 2+ NH4 + The material is almost impossible to embed, resulting in significantly poor optical modulation amplitude and response time performance, making it impossible to obtain effective values during cycle stability testing. Data from numbers 1 to 4 show that as the water content (volume) in the electrolyte solvent increases, the performance of the electrolyte layer gradually improves, but the cycle performance deteriorates sharply when the water content reaches 40%. Therefore, a water content of 30% is the optimal addition amount.
[0080] Data from numbers 5 to 8 show that single zinc ions have a large modulation amplitude but a slow response time, while single ammonium ions have a small modulation amplitude but a fast response time. The mixed ion system can balance both aspects, and the overall performance is optimal when the ratio is 1:1. Under this condition, the cycling stability of the material is the modulation amplitude of the 1000th cycle divided by the modulation amplitude of the 1st cycle.
[0081] Example 3: Based on the comparison in Example 2, the gel electrolyte solution in Serial No. 1 was selected to prepare the electrochromic device.
[0082] The inorganic electrochromic layer in the first transparent conductive electrode / inorganic electrochromic layer prepared in this example was characterized by X-ray diffraction and scanning electron microscopy, respectively. The results are as follows: Figure 2 and Figure 3 As shown.
[0083] Figure 2 In the sample, only two relatively broad diffraction peaks appear at 2θ of 28° and 55°. According to the Scherrer equation, after the grain size enters the nanoscale, the coherent diffraction region shortens, resulting in a significant broadening of the diffraction peaks. Therefore, the WO3 QDs with smaller three-dimensional dimensions only exhibit a broad and weak main peak. The peak positions are consistent with the (200) and (202) crystal planes of hexagonal WO3 (PDF#33-1387), confirming that the product is h-WO3 nanocrystals.
[0084] Figure 3In the study, the thickness of the sprayed film was found to be 419 nm by SEM testing of the cross-section of the film.
[0085] The physical properties of the transparent zinc mesh prepared in this example were characterized using X-ray diffraction and scanning electron microscopy, respectively, and the results are as follows: Figure 4 and Figure 5 As shown.
[0086] Figure 4 The XRD pattern clearly shows the characteristic diffraction peaks of zinc, confirming the successful deposition and good crystallinity of zinc.
[0087] Figure 5 In the SEM images, the overall morphology of the zinc mesh is meticulously depicted, showing that zinc particles are uniformly covered on the surface of the stainless steel mesh without significant dendrite growth. This is attributed to the effective regulation of deposition kinetics by the introduction of PEI additives.
[0088] The electrochromic properties of the inorganic electrochromic layer prepared in this embodiment were tested using the following method: A first transparent conductive electrode / inorganic electrochromic layer was used as the working electrode; zinc foil was used as the counter electrode. Voltages of 1.5V, 0.6V, and 0.1V were applied respectively, and the transmittance of the WO3QDs electrochromic layer to different wavelengths of light under different voltages was tested. Figure 6 As shown; and the response time diagrams of the WO3QDs electrochromic layer when 1.5V and 0.1V voltages are applied under 633nm wavelength light are shown in the figure. Figure 7 As shown.
[0089] Depend on Figure 6 It can be seen that the WO3QDs electrochromic layer has excellent electrochromic performance. It is in a fading state at 1.5V and a colored state at 0.1V, and has a large modulation range. The modulation range of the WO3QDs electrochromic layer for 633nm wavelength light is 88.8% (the difference in transmittance between 1.5V and 0.1V); the modulation range for 1000nm wavelength light is 90.4%; and at 0.6V, the WO3QDs electrochromic layer has selective modulation performance. At this time, the visible light transmittance is high, while the near-infrared transmittance is very low, which can realize independent modulation of visible light and near-infrared light.
[0090] Depend on Figure 7 It can be seen that the response time of the WO3QDs electrochromic layer is: coloring time is 10.6s, and fading time is 6.8s. Therefore, it is evident that the WO3QDs electrochromic layer provided in this embodiment of the invention has a fast response speed to 633nm wavelength light.
[0091] The electrochromic performance of the electrochromic device prepared in this embodiment was tested. Voltages of 1.5V, 0.6V, and 0.1V were applied to the device, and the transmittance spectra of the electrochromic device were measured as follows: Figure 8As shown; and the response times of the device when 1.5V and 0.1V voltages are applied under 633nm wavelength light, as shown. Figure 9 As shown.
[0092] Depend on Figure 8 It is known that the electrochromic device has excellent electrochromic performance. When the voltage is 1.5V, it is in a fading state and when it is in a colored state, it still has a large modulation range. The modulation range of the device at 633nm is 52.6% (the difference in transmittance between 1.5V and 0.1V), and the modulation range of the device at 1000nm is 46.4%. In addition to having high transmittance and high blocking rate states in near-infrared and visible light at 1.5V and 0.1V, the electrochromic device prepared by this invention can also achieve 78.4% blocking of near-infrared light and 34.7% transmission of visible light at 0.6V, thereby realizing independent modulation of visible light and near-infrared light.
[0093] Depend on Figure 9 It can be seen that the response time of the electrochromic device is 2.4 s for coloring at 633 nm and 2.7 s for fading. Therefore, the electrochromic device prepared in this invention has a fast response speed.
[0094] The electrochromic device was photographed using a digital camera at three voltages, and the results are as follows: Figure 10 As shown.
[0095] Depend on Figure 10 It can be seen that at 1.5V and 0.1V, near-infrared and visible light have high transmittance and high blocking rates, respectively. At 0.6V, most of the near-infrared light is blocked while most of the visible light is transmitted, thus achieving independent control of visible and near-infrared light.
[0096] The cycling performance of the electrochromic device prepared in this embodiment was tested using an arbitrary constant potential step wave method (applied voltage of 1.5V for 10s and applied voltage of 0.1V for 10s). The results are as follows: Figure 11 As shown.
[0097] Depend on Figure 11 It can be seen that after 2000 cycles, the electrochromic device still has 81.1% capacity retention, indicating that the electrochromic device of the present invention has excellent cycle life.
[0098] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. An electrochromic device, comprising: The device comprises, from top to bottom, a first transparent conductive electrode, an inorganic electrochromic layer, an electrolyte layer, an ion storage layer, and a second transparent conductive electrode; characterized in that: the first transparent conductive electrode includes a first transparent substrate layer and a first conductive layer, wherein the first transparent substrate layer is located at the top layer of the device, and the first conductive layer is bonded to the inorganic electrochromic layer; the second transparent conductive electrode includes a second transparent substrate layer and a second conductive layer, wherein the second transparent substrate layer is located at the bottom layer of the device, and the second conductive layer is bonded to the ion storage layer.
2. The electrochromic device according to claim 1, characterized in that: The materials of the first transparent substrate layer and the second transparent substrate layer are selected from one or more of glass, quartz, polymethyl methacrylate, polycarbonate, and polyethylene terephthalate.
3. The electrochromic device according to claim 1, characterized in that: The materials of the first conductive layer and the second conductive layer are selected from any one or more of ITO, FTO, AZO, metal, conductive polymer, and carbon nanotubes.
4. The electrochromic device according to claim 1, characterized in that: The sheet resistance of the first and second conductive layers is 5~20Ω / square, and the thickness is 100~300nm.
5. The electrochromic device according to claim 1, characterized in that: The inorganic electrochromic layer has a thickness of 100~1500nm, and the material of the inorganic electrochromic layer is selected from any one or more of tungsten oxide quantum dots, molybdenum oxide quantum dots, vanadium oxide quantum dots and titanium oxide quantum dots.
6. The electrochromic device according to claim 1, characterized in that: The thickness of the electrolyte layer is 100~2000µm, and the cation in the electrolyte layer is NH4. + Zn 2+ The method for preparing the electrolyte layer includes the following steps: S1: A solvent is obtained by mixing trimethyl phosphate and water; S2: Add zinc salt and ammonium salt as electrolytes to the solvent of S1 and stir to obtain an electrolyte solution; S3: Add polyethylene glycol diacrylate and photoinitiator to the electrolyte solution in S2, stir until homogeneous to obtain a gel electrolyte solution, and polymerize under ultraviolet light to obtain an electrolyte layer.
7. The electrochromic device according to claim 6, characterized in that: In S1, trimethyl phosphate and water are mixed in a volume ratio of 7:
3.
8. The electrochromic device according to claim 6, characterized in that: In S2, the zinc salt is zinc trifluoromethanesulfonate and the ammonium salt is ammonium trifluoromethanesulfonate; in the electrolyte solution, the zinc ion concentration is 0.5M and the ammonium ion concentration is 0.5M.
9. The electrochromic device according to claim 1, characterized in that: The thickness of the ion storage layer is 0.1~10μm; the material of the ion storage layer is selected from any one or more of the following: metal electrode, polyaniline electrode, nickel oxide electrode and Prussian blue electrode.
10. The method for preparing the electrochromic device according to any one of claims 1 to 9, characterized in that: Includes the following steps: Step 1: Prepare an inorganic electrochromic layer on the surface of the first conductive layer of the first transparent conductive electrode to obtain the first transparent conductive electrode / inorganic electrochromic layer; Step 2: An ion storage layer is prepared on the surface of the second conductive layer of the second transparent conductive electrode to obtain the ion storage layer / second transparent conductive electrode; Step 3: Seal the first transparent conductive electrode / inorganic electrochromic layer and the ion storage layer / second transparent conductive electrode to form a hollow sandwich structure; then inject a gel electrolyte solution into the cavity of the hollow sandwich structure and solidify it to form an electrolyte layer, thus obtaining the electrochromic device.